Chronic occupational exposure to hexavalent chromium causes DNA damage in electroplating workers - Ren Xiao-Bin; Chen Qing; Yang Zhang-Ping; Jiang Cai-Xia; Jin Li-Fen; Wang Xu-Chu; Zhang Xuan; Zhang Xu-Hui; Cao Jian-Zhong; Wang Qiang; Zhu Yi-Min (BMC, 2011)
Abstract Background Occupational exposure to chromium compounds may result in adverse health effects. This study aims to investigate whether low-level hexavalent chromium (Cr(VI)) exposure can cause DNA damage in electroplating workers. Methods 157 electroplating workers and 93 control subjects with no history of occupational exposure to chromium were recruited in Hangzhou, China. Chromium levels in erythrocytes were determined by graphite furnace atomic absorption spectrophotometer. DNA damage in peripheral lymphocytes was evaluated with the alkaline comet assay by three parameters: Olive tail moment, tail length and percent of DNA in the comet tail (tail DNA%). Urinary 8-OHdG levels were measured by ELISA. Results Chromium concentration in erythrocytes was about two times higher in electroplating workers (median: 4.41 μg/L) than that in control subjects (1.54 μg/L, P < 0.001). The medians (range) of Olive tail moment, tail length and tail DNA% in exposed workers were 1.13 (0.14-6.77), 11.17 (3.46-52.19) and 3.69 (0.65-16.20), and were significantly higher than those in control subjects (0.14 (0.01-0.39), 3.26 (3.00-4.00) and 0.69 (0.04-2.74), P < 0.001). Urinary 8-OHdG concentration was 13.65 (3.08-66.30) μg/g creatinine in exposed workers and 8.31 (2.94-30.83) μg/g creatinine in control subjects (P < 0.001). The differences of urinary 8-OHdG levels, Olive tail moment, tail length and tail DNA% between these two groups remained significant (P < 0.001) even after stratification by potential confounding factors such as age, gender, and smoking status. Chromium exposure was found to be positively associated with chromium levels in erythrocytes, urinary 8-OHdG levels, Olive tail moment, tail length and tail DNA%. Positive dose-response associations were also found between chromium levels in erythrocytes and Olive tail moment, tail length and tail DNA%. Conclusion The findings in this study indicated that there was detectable chromium exposure in electroplating workers. Low-level occupational chromium exposure induced DNA damage.